A high-performance catalyst support for methanol oxidation with graphene and vanadium carbonitride. Issue 4 (15th December 2014) - Huang, Taizhong; Mao, Shun; Zhou, Guihua; Zhang, Zhaoliang; Wen, Zhenhai; Huang, Xingkang; Ci, Suqin; Chen, Junhong
Abstract : A graphene–V(C, N) support promotes the catalytic performance of Pt nanoparticles in methanol oxidation. Abstract : In this study, a graphene–vanadium carbonitride (G–V(C, N)) hybrid is reported as a novel support for the Pt catalyst in methanol oxidation. The catalytic activity of the Pt/G–V(C, N) hybrid for methanol oxidation is greatly enhanced compared with that of a commercial Pt/C catalyst with carbon black as the catalyst support. The outstanding catalytic activity of the Pt/G–V(C, N) catalyst suggests the potential of using graphene–metal carbonitride as the catalyst support in fuel cells.